Investigating Industry Payments of OB/GYN Practice Bulletin Committee Members and Contributing Authors [5I]. (May 2018) - Wright, Micah; Checketts, Jake; Vassar, Matt; Guevara, Carlos; Smith, Larissa; Frye, Lance
Abstract : INTRODUCTION: Our study evaluates payments received by ACOG Obstetrics and Gynecology practice bulletin committee members, physicians who author the ACOG Obstetrics and Gynecology practice bulletins, and for comparison the authors of an ACOG established Task Force on Hypertension guideline, compares disclosure statements for accuracy, and determines whether the pharmaceutical companies from which authors received payments manufactured products related to the guidelines. We also investigate payments from top contributors and ties to the specialty METHODS: We conducted a cross-sectional study of the Open Payments database. We limited our search from 2014 to present (Open Payment data are not available prior to 2014). We included all general payments and research payments reported from 2014-2015, which included direct payments, indirect payments or other transfers of value made to physicians by applicable manufacturers. We calculated total general payments and also research payment averages and ranges and averages within each group of authors separately RESULTS: Of the 60 authors evaluated, 34 received at least one reported industry payment. In total general financial payments amounted to 289, 407.36 with a mean of 977.73 per author. Of the 34 authors receiving payments, only 2 authors received specific research payments. Top contributing companies were identified and products related to the specialty were listed. CONCLUSION: In absence of other factors, such as level of evidence, financial conflicts do not seem to play a large role in ACOG practice bulletin limitations. Evaluation of the structure of practice bulletin committees would suggest that a large amount of influence is controlled by only a select few.